HUBUNGAN DUKUNGAN EMOSIONAL TEMAN SEBAYA DENGAN KUALITAS HIDUP LANSIA DI UPT PELAYANAN SOSIAL TRESNA WERDHA JEMBER: The Relationship of Peer Emotional Support with the Elderly Quality Life at UPT Tresna Werdha Social Service Unit in Jember - Akbar Ibrahim Akbar; Sofia Rhosma Dewi; Yeni Suryaningsih (Forind Press, 2024)
The emotional support of peers is a very valuable thing to show concern and affection for each other, especially the elderly who are in social institutions because all they have are friends, no more family. Strong peer emotional support for the elderly will have an impact on the quality of life of the elderly because the elderly will be comfortable, peaceful and feel loved when experiencing stress, as well as making the elderly feel appreciated and important. This research is a quantitative study with a cross sectional approach which aims to identify the relationship between emotional support from peers and the quality of life of the elderly at UPT PSTW Jember with a total of 47 respondents. The sampling technique uses purposive sampling. The results of the research show that the results of the analysis of the respondents studied, the majority of emotional support from peers is ineffective emotional support as many as 28 (59.6%) and the quality of life of the elderly at UPT PSTW Jember is at moderate quality of life as many as 41 (87.2% ). Then the Spearman's rho test results show a p value of 0.000, which means there is a relationship between the emotional support of peers and the quality of life of the elderly. The recommendation for this research is to pay more attention to the quality of life of the elderly by becoming a liaison between the elderly and their peers to create a good relationship or interaction so that emotional support can be received effectively.